Formulation and Physical Stability Test of Shampoo Preparation Combination of Ethanol Extract of Jackfruit Leaves (Artocarpus heterophyllus) and Pandan Leaves (Pandanus Amaryllifolius) with Varying Carbomer Concentrations - Kessya, Febrilliani Kharisma; Pratiwi, Rosaria Ika; Febriyanti, Rizki (Indonesian Journal of Chemical Science and Technology (IJCST), 2024)
Hair plays an important role for humans because hair can influence a person's appearance. Pandan leaves (Pandanus Amaryllifolius) contain compounds in the form of alkaloids, flavonoids, saponins, polyphenols, tannins and dyes. In pandan leaves, the compounds that can provide antimicrobial activity are flavonoids and polyphenols (phenols). This research aims to formulate and test the physical stability of a shampoo combining ethanol extract of jackfruit leaves (Artocarpus heterophyllus) and pandan leaves (Pandanus Amaryllifolius) with varying carbomer concentrations. This research method is laboratory experimental. The carbomer concentration used is 0.1%, 0.3%, 0.5%. The research results showed that the shampoo preparation with the best carbomer concentration was formula 3 with a carbomer concentration of 0.5%. Viewed from an organoleptic perspective, namely with a blackish brown color, the typical smell of pandan accompanied by menthol, pH 6, the shampoo preparation obtained is homogeneous and produces the best foam, namely 13.5 cm in formula 3. Keywords: Shampoo, anti-dandruff, pandan leaves, jackfruit leaf extract.